KRITIS CENDIKIAWAN MUSLIM TERHADAP PENAFSIRAN QURAISH SHIHAB TENTANG JILBAB - Sagitarius, Nandra; Suhandi, Tjeptjep (IBN KHALDUN BOGOR, 2013)
The Qur'an interpreter Quraish Shihab provide conclusions and different interpretations of the religious establishment in providing legal arguments about the veil. He said that the head is not the nakedness because he thinks that the provisions will limit tolerable from the genitalia or female body is zhanniy not qathi ', in addition to the Qur'anic verse provides no details clearly and forcefully about the limits of the genitalia, such as what is mentioned in the Qur'an Surah An-Nur verse 31 and Surah Al-Ahzab verse 59. from these different thoughts, arise wide criticism from Muslim scholars to the thought of Quraish Shihab.